2020
DOI: 10.20344/amp.12082
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Different Patient Information Sources to Create the Best Possible Medication History

Abstract: Introduction: Obtaining the best possible medication history is the crucial step in medication reconciliation. Our aim was to evaluate the potential contributions of the main data sources available – patient/caregiver, hospital medical records, and shared electronic health records – to obtain an accurate ‘best possible medication history’.Material and Methods: An observational cross-sectional study was conducted. Adult patients taking at least one medicine were included. Patient interview was performed upon ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Assim, tendo em vista aprofundar este conhecimento a nível nacional, Oliveira e colaboradores (2020) avaliaram as potenciais contribuições das principais fontes de informação disponíveis em Portugal na obtenção da BPMH, demonstrando a importância dos registos eletrónicos em saúde, representados nomeadamente pela plataforma de dados da saúde (PDS), na maior exatidão da informação terapêutica, particularmente ao se considerar um período retrospetivo de seis meses ao internamento. 7 Na continuidade deste trabalho, foi nosso objetivo realizar um estudo-piloto de Reconciliação Terapêutica no momento da admissão hospitalar para, a partir dele, identificarmos os recursos necessários para a sua implementação na prática clínica.…”
unclassified
See 1 more Smart Citation
“…Assim, tendo em vista aprofundar este conhecimento a nível nacional, Oliveira e colaboradores (2020) avaliaram as potenciais contribuições das principais fontes de informação disponíveis em Portugal na obtenção da BPMH, demonstrando a importância dos registos eletrónicos em saúde, representados nomeadamente pela plataforma de dados da saúde (PDS), na maior exatidão da informação terapêutica, particularmente ao se considerar um período retrospetivo de seis meses ao internamento. 7 Na continuidade deste trabalho, foi nosso objetivo realizar um estudo-piloto de Reconciliação Terapêutica no momento da admissão hospitalar para, a partir dele, identificarmos os recursos necessários para a sua implementação na prática clínica.…”
unclassified
“…Obtenção do perfil farmacoterapêutico pré-hospitalar e construção da BPMH. Além dos registos hospitalares, foram consultados o Registo de Saúde Eletrónico (RSE) na Plataforma de Dados da Saúde (PDS) num período retrospetivo de seis meses a contar da data de admissão hospitalar, 7 prescrições médicas de ambulatório, listas e sacos de medicação trazidos pelo doente ou das instituições de longa permanência, assim como demais prescrições, planos de Para finalizar esta etapa, o farmacêutico-investigador realizou uma entrevista semiestruturada a todos os participantes (doente/cuidador) com vista à confirmação dos dados obtidos, considerando-se esta informação como sendo a mais exata. Feita a confrontação dos dados obtidos na entrevista com, pelo menos, mais uma das fontes de dados citadas, construímos a BPMH, permitindo a identificação dos medicamentos de uso crónico pré-hospitalar (nome do medicamento, dose, forma farmacêutica, frequência e via de administração).…”
unclassified
“…Another important aspect is the fact that some PRFs may be available in the nursing records (e.g., blood pressure, weight), which may be missed if prescribers do not look for it when prescribing atypical APs, where the risk of developing metabolic syndrome is high. So, it is important to acknowledge the contribution of different patient information sources to ensure a safe prescribing of such medications (27).…”
Section: Main Findingsmentioning
confidence: 99%
“…1 MR is a systematic process to create an accurate list of the patient’s medicines, known as the best possible medication history, and to compare it with the medication instituted at each time of transition of care. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…1 MR is a systematic process to create an accurate list of the patient's medicines, known as the best possible medication history, and to compare it with the medication instituted at each time of transition of care. 2,3 In many countries, healthcare institutions should have established medication reconciliation policies at patient admission. 4,5 The Prescribing Observatory for Mental Health in the UK, which aims to improve the quality of mental health prescribing practice, reported that medication reconciliation improves the quality of these inpatient health programs in a psychiatric unit.…”
Section: Introductionmentioning
confidence: 99%